Applications of hydrodynamic cavitation for instant rehydration of high protein milk powders. (May 2018) - Pathania, Shivani; Ho, Quang Tri; Hogan, Sean A.; McCarthy, Noel; Tobin, John T.
Abstract: The aim of this study was to evaluate the effectiveness of an in-line hydrodynamic cavitation (HC) system, for rehydration of milk protein concentrate powders (MPC) at semi-industrial pilot scale. MPC powder was dispersed in water at 50 °C at 20% (w/w) dry matter (DM) with two commonly used high-shear powder inductors/mixers. The MPC dispersions created were then passed through the HC system to assess subsequent hydration behaviour of the MPC powders. Particle size distribution (PSD) of MPC dispersions prepared using conventional high-shear mixing indicated that complete rehydration of MPC powders was not achieved, with an average D90 and D[4, 3] values of 21.17 μm and 5.62 μm respectively, observed in MPC dispersions. In contrast MPC dispersions subjected to HC had a PSD indicative of complete rehydration, with an average D90 and D[4, 3] values of 0.45 μm and 0.19 μm, respectively. Apparent viscosity decreased significantly ( p ≤. 05 ) post HC compared to dispersions subjected to conventional high shear mixing. Phase separation profiles showed that HC treated MPC dispersions had increased stability to sedimentation compared to high-shear treated samples. Wetting, immersion, dissolution and solubilisation of high protein powders occurred instantaneously (and simultaneously) during HC. This emerging technology has the potential to achieve complete rehydration of powders in significantly less time than conventional rehydration processes employed by dairy and other industries. Highlights: Instant rehydration of MPC80 was studied at 20% (w/w) dry matter content. Hydrodynamic cavitation (HC), as a novel technology, is assessed to improve hydration kinetics of high protein powders. HC significantly reduces the viscosity, particle size distribution and increases stability of rehydrated MPC solutions. Wetting, immersion, dissolution and solubilisation of powder particles occur instantaneously and simultaneously during HC.